Frontiers of the Roman Empire : The Upper Germanic Limes : Grenzen des Römischen Reiches: Der Obergermanische Limes / Frontières de l´Empire Romain: Le limes de Germanie supérieure /: The Upper Germanic Limes : Grenzen des Römischen Reiches: Der Obergermanische Limes / Frontières de l´Empire Romain: Le limes de Germanie supérieure. (2022) - Breeze, David J; Thiel, Andreas; Roth, Sarah; Becker, Thomas
No abstract available